Criminal Management for Protective Support of Free Access to Information with a Perspective on Filtering - Amirian Farsani, Amin (Digital Transformation and Administration Innovation, 2027)
Criminal management aimed at protective support for free accessibility to information represents an emerging approach that links the domains of criminal justice and data-driven governance. Its purpose is to establish a balance between the security imperatives of the criminal justice system and the fundamental right of citizens to know and to exercise public oversight. Grounded in the principles of transparency, accountability, and public participation, this concept seeks to enhance public trust in criminal justice institutions through improving the level of information dissemination. Within this framework, criminal management evolves from a purely reactive and punishment-oriented structure toward an intelligent, restorative, and protective system. In protective criminal management, non-confidential criminal information (such as crime statistics, institutional performance measures, and prevention indicators) is employed as an instrument of soft deterrence and social supervision. This approach, in addition to promoting transparency and efficiency, remains committed to safeguarding the privacy rights of victims and defendants. The present study, using an analytical–comparative method, examines the theoretical foundations of the “right to free access to information” and its impact on criminal justice in international instruments and in Iran’s legal system. It further analyzes the existing structural deficiencies in the implementation of the Law on the Publication and Free Access to Information enacted in 2009. The findings indicate that achieving protective criminal management requires data integration among judicial and law-enforcement bodies, the formulation of judicial transparency regulations, and the institutionalization of a culture of accountability. Ultimately, such a model can provide an innovative framework for data-based, community-oriented criminal justice rooted in open governance within Iran’s legal system.